Solvent Extraction Of Lanthanide (III) With Dibenzo-[24]-Crown-8 From Aqueous Picrate Solution - Mohamed Ali, Abdussalam Salhin (1994)
A systematic study of the extraction of fourteen metals, namely yttrium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, erbium, thulium, ytterbium and lutetium, from picrate media [(N02)3.C6H2.0H] was carried out with dichloromethane solution containing various crown ethers namely, dibenzo-[24]-crown-8, dicyclohexano-[24]-crown-8 and . dibenzo-[30]-crown-10. The optimum condition for the separation of these elements was studied.